Atrial Fibrillation Detected before or after Stroke: Role of Anticoagulation - Lyrer, Flurina; Zietz, Annaelle; Seiffge, David J.; Koga, Masatoshi; Volbers, Bastian; Wilson, Duncan; Bonetti, Bruno; Schaedelin, Sabine; Gensicke, Henrik; Yoshimura, Sohei; Macha, Kosmas; Ambler, Gareth; et al. (Annals of Neurology, 2023)
Background: Atrial fibrillation (AF) known before ischemic stroke (KAF) has been postulated to be an independent category with a recurrence risk higher than that of AF detected after stroke (AFDAS). However, it is unknown whether this risk difference is confounded by pre-existing anticoagulation, which is most common in KAF and also indicates a high ischemic stroke recurrence risk. Methods: Individual patient data analysis from 5 prospective cohorts of anticoagulated patients following AF-associated ischemic stroke. We compared the primary (ischemic stroke recurrence) and secondary outcome (all-cause death) among patients with AFDAS versus KAF and among anticoagulation-naïve versus previously anticoagulated patients using multivariable Cox, Fine-Gray models, and goodness-of-fit statistics to investigate the relative independent prognostic importance of AF-category and pre-existing anticoagulation. Results: Of 4,357 patients, 1,889 (43%) had AFDAS and 2,468 (57%) had KAF, while 3,105 (71%) were anticoagulation-naïve before stroke and 1,252 (29%) were previously anticoagulated. During 6,071 patient-years of follow-up, we observed 244 recurrent strokes and 661 deaths. Only pre-existing anticoagulation (but not KAF) was independently associated with a higher hazard for stroke recurrence in both Cox and Fine-Gray models. Models incorporating pre-existing anticoagulation showed better fit than those with AF category; adding AF-category did not result in better model fit. Neither pre-existing anticoagulation nor KAF were independently associated with death. Conclusion: Our findings challenge the notion that KAF and AFDAS are clinically relevant and distinct prognostic entities. Instead of attributing an independently high stroke recurrence risk to KAF, future research should focus on the causes of stroke despite anticoagulation to develop improved preventive treatments. ANN NEUROL 2023.
CRIS-Team Scopus Importer:2023-04-28